22. Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD 1 Panjang - Pambudi, Andik Arry; Prasetyowati, Dina; Utami, Sri (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
This research have aim to describe the using of learning model Problem Based Learning finding the increasing learning of result Civic education at class III SD 1 Panjang Kudus regency. Design this research was conducted through the planning stage of the action, observation, and reflection. This research was conducted as two cycles with each cycle consisting of two meetings. Topic the research is teacher and student at class IV SD 1 Panjang Kudus. Variable that research is teacher ability, student activity, and the result of student learning. Kind of data: Qualitative and Quantitative. The research of data: Teacher, student and documentation. Techniques of data retrieval include techniques of test and non- test. Technique analysis of data is using descriptive analysis technique. The result of that research show that with using a model Problem Based Learningt could increase of cognitive learning also increases seen from the improvement in cycle I to cycleII namely from 69% to 85%.